GLOBAL SARS-CoV-2 PANDEMIC: THE IMPACT ON LIBRARIES - Abulude, Ifeoluwa Ayodeji; Gbotoso , Arinola Oluwatoyin; Abulude, Francis Olawale (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The library is one of the sections in an educational sector that contributes to knowledge. Most of the libraries worldwide operate on a 24-hr basis, but a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic came and ravaged many countries of the world and turned their libraries into ‘ghost‘ arenas for about eight months. To protect the stakeholders (students, lecturers, staff, and visitors) from the infection of the virus, the management of each institution and associations ordered the partial or total closure of the libraries until the official announcement of the reduction of the risk from SARS-CoV-2. To ensure continuous contacts to the library, many libraries have resulted in the use of virtual methods where they provide e-books, e-journals, e-magazines, and many others to those who require the services. The objective of this work is to present a systematic review of the effects the pandemic has on the libraries and the stakeholders and the preparations for re-opening partially or fully.